THE LINGUISTIC INTERPRETATION OF POETIC DISCOURSE: FROM TEXT TO DISCOURSE - Ortiqov Eldor Mardonovich (Innovate Conferences, 2026)
This article examines the theoretical foundations of poetic discourse as a systemic phenomenon within the shift from text linguistics to discourse linguistics. The study focuses on speech act theory, the correlation between the concepts of “text” and “discourse,” and their reinterpretation within the cognitive-discursive paradigm. Drawing on the works of M. Halliday, I. M. Kobozeva, and N. D. Arutyunova, the paper highlights the distinction between text as a static product of speech activity and discourse as a dynamic, socially and pragmatically conditioned process. Special attention is paid to cognitive linguopoetics, poetic linguistic personality, intertextuality, and precedent phenomena as essential components of the discursive space of poetic texts. The research substantiates the non-binary opposition between text and speech in modern linguistics and emphasizes their functional and cognitive unity.
Keywords: text, discourse, speech act, cognitive-discursive paradigm, poetic speech, linguopoetics, intertextuality, precedent phenomenon